Philosophy and Neurosciences: Perspectives for Interaction - Vadim A. Chaly (RUDN Journal of Philosophy, 2023)
The study analyzes modern reductivist and antireductivist approaches to understanding the interaction between philosophy and neuroscience. It analyzes the content and grounds for using the concepts of neuroscience and neurosciences, philosophy of neuroscience, and neurophilosophy. The milestones in the development of neuroreductivism, from Patricia Churchland’s arguments in support of intertheoretic reduction through Francis Crick’s eliminativism to John Bickle’s ruthless reductionism, are described. The ontological, methodological, and epistemic grounds for the reduction to neurosciences of other ways of representing mind and body are analyzed. Drawing on the post-Wittgensteinian paradigm of the philosophy of neuroscience of Max Bennett, Peter Hacker, and Andrew Reynolds, the semantic problems that arise in the neurosciences when epistemic reduction is attempted are described and derive from the inability to eliminate the basic metaphorical level of meaning-making and transmission rooted in everyday language and its figures, among which metaphors are fundamental. The descriptivist approach to the language of neurosciences is contrasted with neurorevisionism, an attempt to “correct” established ways of conceptualizing consciousness and corporeality, akin to earlier revisionisms, particularly physicalism, and forced to deal with similar problems. Reduction - the operation of the “return,” itself understood metaphorically - and antireduction, which resists scientific revisionism and “returns” understanding to the level of everyday language and philosophy to descriptive work, is presented as a circular hermeneutical movement necessary for scientific and philosophical understanding, but not leading to disciplinary hegemony or the “victory” of either side. The study concludes with a sketch of the publications included in the rubric.